Pemberdayaan Pemuda melalui Penguatan Organisasi Karang Taruna di Desa Dayak Pitap Kabupaten Balangan - Noor Anisa Septiana; Budhi, Setia; Arfinda, Dhea; Novitasari; Kamaliah, Nur; Aulia, Miftahul; Al’Inayah, Amalia Ayu; Akila, Kesa; Azzein, Muhammad Haris; Hendriani, Rahmat Jayannor; Mubarak, Muhammad Fathul (Prodi Sosiologi FISIP ULM, 2025)
Social changes in rural communities require young people to play an active role as agents of change in social and cultural development. However, in Dayak Pitap Village, youth participation remains low due to the Karang Taruna youth organization not functioning optimally. This study aims to revitalize the role of youth through the establishment and strengthening of the Karang Taruna “Iyam Mitra Muda” organization as a forum for nurturing the younger generation in the social, cultural, and leadership fields. The main programs implemented include organizing institutional structures, formulating vision, mission, and statutes, improving managerial capacity, and fostering a pioneering spirit through social and cultural activities. The results of these activities show a significant increase in the administrative, coordination, and leadership abilities of young people, accompanied by a growing collective awareness of the importance of their participation in village development. Through various activities such as Indonesian Independence Day celebrations, PBB/Linmas training, and involvement in traditional ceremonies, young people have become more active, disciplined, and united in carrying out their social roles. In addition, the formation of a clear organizational structure and the drafting of AD/ART have become the basis for Karang Taruna to move in a more focused and sustainable direction. From the results of this study, it can be concluded that Karang Taruna “Iyam Mitra Muda” plays a strategic role in strengthening the capacity of youth as the driving force of social development in Dayak Pitap Village. This study is expected to be a reference for the development of youth empowerment models in other villages in a participatory and sustainable manner.